Structural Stability and Optoelectronic Properties of Lead-Free Halide Perovskite CsSnBr3 by Introducing Transition-Metal Dopants - Tang, Fengjie; Yao, Yizhou; Cao, Dan; Yan, Jie; Wang, Jianfeng; Jiang, Zhouting; Zhou, Yun; Jiao, Zhiwei; Shu, Haibo (Journal of electronic materials, 2022)
In order to promote the actual optoelectronic application of lead-free perovskite CsSnBr 3 , the stability and optoelectronic properties of metal dopants in the lead-free perovskite CsSnBr 3 have been studied systematically by using first-principles calculations based on density functional theory. Cd and Mn doping is more efficient in CsSnBr 3 than other considered metal dopants by calculating the doped formation energies. The stability of a doping system is related to the atomic radius of the dopant. Cr, Mn and Cu dopants can enlarge effectively the band gap of CsSnBr 3 and show a higher optical absorption coefficient in short wavelength region of visible light compared to undoped ones. Our work may provide a feasible pathway to manipulate and improve the stability and optoelectronic performance of CsSnBr 3 .